AGRONOMIC CHARACTERISTICS AND PRODUCTIVITY OF SOYBEAN SUBMITTED TO DOSES OF NITROGEN FERTILIZATION AND INOCULATION WITH PANTOEA AGGLOMERANS STRAIN O4 - Leopoldina Sousa, Laura; Theo Gentil, Kevin; Biotech Brasil, Green (Journal of Interdisciplinary Debates, 2021)
The soybean (Glycine max (L.) Merrill) is a prominent crop in the world grain scenario, it is currently cultivated in practically all the Brazilian national territory. Brazil appears as the world's second largest producer of this grain. Soybean cultivation is still the crop that consumes the most fertilizers in Brazil, with Nitrogen being the most required nutrient in the plant. The objective of this study was to evaluate the effect of seed inoculation with Pantoea Agglomerans Strain O4 bacteria and their relationship with nitrogen doses on soybean development and yield. The experiment was carried out in the experimental area of the Center of Agrarian Sciences and Biodiversity (CCAB), Federal University of Cariri (UFCA), in Crato - CE, in a randomized block design, in a subdivided plot, with three replications, thus totaling 24 experimental plots. The plots were four nitrogen doses (0, 25, 50 and 100% of the recommended dose) and the subplots referring to the use of AzotoBarvar inoculant (with and without). The variables analyzed were: plant height, first pod insertion height, number of branches per plant, number of pods per plant, pod per plant mass, mass of 100 grains, grain mass per plant and productivity. The data were submitted to analysis of variance by the F test and the means of the Bavar factor compared by the Tukey test at 5% of probability. The statistical program Sisvar 5.3 was used for the statistical analysis. According to the analysis of variance none of the variables presented significant results, for the interaction Fertilizer*Barvar or for the AzotoBarvar and Fertilizer factors separately. According to the means test, however, it was observed better results for plant height, number of pods per plant, pod mass per plant, grain mass per plant and productivity in the presence of the inoculant.